EDP managing a new electricity era: the birth of ocean winds and strategic partnerships as a tool towards sustainability - Cavaleiro, Catarina Alexandra Cerqueira (2022)
When the renewable energy market started to grow at the beginning of this century, EDPR faced the need to expand its portfolio. Like many other business decisions, entering a new market is not easy. The following paper analyzes the strategic decision of EDPR when deciding either to pursue a partnership or to go alone in the brand-new offshore wind energy sector. It examines the considered factors for the partnership decision to understand how the partnership was established and its potential in the fast-growing offshore wind energy sector.